Infection with Histoplasma capsulatum in a renal transplant recipient - Rekha Arcot; Kindo Anupma; Sounderarajan P; Ravi A (Saudi Journal of Kidney Diseases and Transplantation, 2010)
With the advent of potent immunosuppressive therapies in solid organ trans-plantation, patients are more susceptible to a variety of infections with atypical pathogens and presentations. We report a renal transplant recipient with atypical presentation of histoplasmosis.